Elevated Plasma Homocysteine Concentration in Opium-Addicted Individuals - Masoomi, Mohammad (Addict Health, 2015)
BACKGROUND: Although the triggering role of both opium use and elevated plasma homocysteine level for progressing atherosclerosis and, therefore, appearing coronary heart disease has been clearly determined, no study are available with respect to the relation between these to risk profiles. In the present study and for the first time, we hypothesized that the opium addiction can be potentially correlated with elevated homocysteine concentration. METHODS: 217 persons (103 opium-addicted and 114 non-addicted) were randomly selected from the Kerman Coronary Artery Disease Risk Study (KERCADRS), Iran, as a population-based, epidemiological prospective study. In all participants, an enzyme immunoassay kit was used to measure homocysteine in serum samples. FINDINGS: The serum level of homocysteine was significantly higher in the opium-addicted ones compared to non-addicted individuals (11.49 ± 7.45 vs. 8.02 ± 3.87 μmol/l) (P < 0.001). In this regard, 21.3% of the opium users and only 3.2% of the non-users had homocysteine concentration > 15 μmol/l (P < 0.001). On the other hand, individuals addicted to opiates exhibited significantly elevated odds of having homocysteine level higher than 15 [odds ratio (OR) = 8.244, 95% confidence interval (CI) = 3.117-21.806]. Multivariable linear regression model showed that the opium addiction could strongly predict elevated homocysteine level in the study individuals [beta = 3.524, standard error (SE) = 0.852] (P < 0.001). CONCLUSION: Opium consumption can be strongly accompanied with the elevation of plasma homocysteine concentration, and thus opium addiction can exhibit elevated odds of having hyperhomocysteinemia.